2022
DOI: 10.3389/fphar.2021.728315
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Roles of Metformin in Alzheimer’s Disease: A Snapshot

Abstract: Alzheimer’s disease (AD) is a prevalent neurodegenerative disease predominantly affecting millions of elderly people. To date, no effective therapy has been identified to reverse the progression of AD. Metformin, as a first-line medication for Type 2 Diabetes Mellitus (T2DM), exerts multiple beneficial effects on various neurodegenerative disorders, including AD. Evidence from clinical studies has demonstrated that metformin use contributes to a lower risk of developing AD and better cognitive performance, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 88 publications
0
20
0
Order By: Relevance
“…As was indicated in a 2022 narrative review by Liao et al [397] of the potential role for metformin in offsetting the development of Alzheimer's disease the evidence of benefits remains ambiguous, despite data from preclinical studies providing potential mechanisms of action for metformin as a neuro-protective drug. Furthermore, the data from clinical studies are not universally positive thus raising concerns overextending the use of metformin to patients without T2D.…”
Section: Metformin and Neurodegenerative Diseasesmentioning
confidence: 99%
“…As was indicated in a 2022 narrative review by Liao et al [397] of the potential role for metformin in offsetting the development of Alzheimer's disease the evidence of benefits remains ambiguous, despite data from preclinical studies providing potential mechanisms of action for metformin as a neuro-protective drug. Furthermore, the data from clinical studies are not universally positive thus raising concerns overextending the use of metformin to patients without T2D.…”
Section: Metformin and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Taken together, NF-κB and NLRP3 inflammasome are activated in PD neuropathology and linked with the development of neuroinflammation (Paudel et al 2020 ). It has been shown that antagonistic crosstalk between SIRT1 and NF-κB is present to regulate energy metabolism and innate immunity (Liao et al 2021 ). NF-κB regulates immunity defense while SIRT1 controls inflammatory signaling pathways and cellular survival.…”
Section: Mechanistic Role Of Sirt1 In Pdmentioning
confidence: 99%
“…We cannot ignore the potential role of diabetes medication in AD pathology, especially metformin, which has been reported to decrease dementia risk by reducing vascular risk and to provide neuroprotection independently of glycaemic control 37 ; however, both AHM‐user groups reported a similar frequency of metformin use.…”
Section: Discussionmentioning
confidence: 99%